Students Vocabulary Mastery Based on Their Learning Style: Visual, Auditory and Kinesthetic - Lili Suryani; Sahril Nur; Muh. Tahir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The objective of this research was to find out significant the differences in students’ vocabulary mastery based on their learning style. This research employed a descriptive qualitative method. The subject of this research was seven-grade students of SMPN 4 Patampanua which consisted of 30 students who were taken by using simple random sampling. The instruments in collecting the data were a questionnaire and a test. The data obtained through the questionnaire was to see students’ learning styles and data from the test was to see students’ vocabulary scores. The research used SPSS to get appropriate data. Based on the research findings, the result showed F-value (F˳) is lower than F-table (Ft), (F˳ < F table). Further, the p-value is greater than alpha (ɑ), (p-value > 0.05). As a result, H˳ is accepted if F-value (F˳) < F-table (Ft) and probability significant (sig.) value > 0.05. Therefore, it can be concluded that there is no significant difference in students’ vocabulary mastery based on their learning styles.